1963
DOI: 10.1002/j.1537-2197.1963.tb07209.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Ontogeny of the Dwarf Mistletoes, Arceuthobium. Ii. Homology of the Endophytic System

Abstract: Cohen, L. I. (Washington State U., Pullman.) Studies on the ontogeny of the dwarf mistletoes, Arceuthobium. H. Homology of the endophytic system. Amor. Jour. Bot. 50(5): 409–417. Illus. 1963.—Development of the seedling in Arceuthobium, as well as the mode of penetration and infection, is described. The promeristem of the root apex of the seedling, as in the embryo, is composed of 4 zones: (1) a uniseriate layer of apical surface initials; (2) a subapical zone of central initials; (3) a peripheral zone; and (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1964
1964
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…Once in contact with phellem, the penetrating structure ramified into filaments. Although surface initials at the leading edge of the penetrating structure participated in penetration, the penetration process was more than just surface initials initiating infection, as reported by Cohen (1963), or the radicle promeristem apparently growing into bark fissures as reported by Tainter (1971). Formation of the penetrating structure and its method of penetration is almost identical to that reported for needles of Abies spp.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Once in contact with phellem, the penetrating structure ramified into filaments. Although surface initials at the leading edge of the penetrating structure participated in penetration, the penetration process was more than just surface initials initiating infection, as reported by Cohen (1963), or the radicle promeristem apparently growing into bark fissures as reported by Tainter (1971). Formation of the penetrating structure and its method of penetration is almost identical to that reported for needles of Abies spp.…”
supporting
confidence: 55%
“…However, only the existence of mechanical forces that crush host cells was demonstrated in dwarf mistletoe penetration (Kuijt 1960, Cohen 1963, Scharpf & Parmeter 1967). Parmeter and Platt (1968) demonstrated that A. abiet-…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may indicate a change in the mechanism of transport possibly related to the absence of (5,6,16,28). When mistletoe shoots were girdled by exposing a portion of the stem to steam, host photosynthate failed to move through the injured tissue and the shoots subsequently died.…”
Section: Methodsmentioning
confidence: 99%
“…Injury caused by dwarf mistletoe is manifested in a variety of ways: reduction in tree growth, distortion of growth, recluction in wood quality, predisposition of trees to secondary attack, and reduction in seed yield seems less direct in Phoradendron (4,34). Differentiated phloem tissue has never been observed in Arceuthobium (5,6,16,28) and in Phoradendron it is present only in the aerial shoots (34). There appears to be no specialized relationship between the phloem of the host and the endophytic system of either Arceuthobium ( 5,9,22) or Phoradendron (4,34).…”
Section: Introductionmentioning
confidence: 99%